2020
DOI: 10.3390/ma14010028
|View full text |Cite
|
Sign up to set email alerts
|

Double-Inverse-Opal-Structured Particle Assembly as a Novel Immobilized Photocatalytic Material

Abstract: Immobilization of photocatalysts on supports is an important method of adding highly active photocatalysts to a continuous flowing system without the need for photocatalyst recovery. However, direct immobilization prevents exposure to all photocatalytically active surfaces. Therefore, to immobilize particulate photocatalysts, while exposing the photocatalytic surface to organic pollutant water in a continuous flowing system, in this study, we employed double-inverse-opal (DIO) with periodically arranged, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…This approach can be further enhanced by deposition of co-catalysts ( i.e. , noble metal and semiconductors) via decoration with nanoparticles, atomic layer deposition (ALD), and sol–gel method. For instance, Sopha et al demonstrated a photocatalytic enhancement of ∼72% in photodegrading MB under UV light illumination after precisely depositing TiO 2 nanotubes with uniform TiO 2 coatings of 11 nm thickness by ALD . Organic breakdown enhancements were attributed to the efficient charge carrier separation of the ALD-derived TiO 2 coating, which is strongly supported by a high specific surface area of TiO 2 nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can be further enhanced by deposition of co-catalysts ( i.e. , noble metal and semiconductors) via decoration with nanoparticles, atomic layer deposition (ALD), and sol–gel method. For instance, Sopha et al demonstrated a photocatalytic enhancement of ∼72% in photodegrading MB under UV light illumination after precisely depositing TiO 2 nanotubes with uniform TiO 2 coatings of 11 nm thickness by ALD . Organic breakdown enhancements were attributed to the efficient charge carrier separation of the ALD-derived TiO 2 coating, which is strongly supported by a high specific surface area of TiO 2 nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…The details of each procedure and synthesized particles are presented in the Supporting Information. The heat treatment also promotes the crystallization of TiO 2 from the amorphous to anatase phase, 50 which increases the refractive index. Because the core particles were stuck on the inner wall of silica shells after the heat treatment, the inner silica shell walls were dissolved slightly in NH 3 aq (pH ∼11).…”
Section: Synthesis Of Yolk−shell Particles Incorporating a S/t/s Corementioning
confidence: 99%
“…Double inverse opal structures have also been proposed as a method to confine particulate photocatalysts to a structure without decreasing the active surface area. [ 392 ] From examples in the literature, photocatalysts are frequently structured as 3DOMs, both for the structural advantages of the macroporous structure and optical phenomena such as the slow photon effect, see Section 3 for more details.…”
Section: Photonic Crystal Structural Porosity and Interconnectivity A...mentioning
confidence: 99%
“…[425,426] X-ray diffraction, microscopy techniques, neutron analysis, scanning probe microscopy, Raman and FTIR spectroscopy are among some of the techniques currently utilized for operando monitoring of lithium-ion batteries. Current research shows ongoing efforts to improve the quality, scale, and design of photonic crystal films through mixed oxide precursors, [136] precursor coassembly with crystalline nanoparticles, [427,244] increased film wettability during assembly, [428] particle-nested double inverse opal structures [392,429,430] and photonic crystal heterostructures with varying lattice size [134,431,432] or material composition. [239,433,434] These various strategies show a concerted effort to achieve large-scale crack-free IO photonic crystal films with a strong optical signature.…”
Section: Conclusion and Outlook On The Role Of Photonic Crystal Mater...mentioning
confidence: 99%